2(5n-8)-5n=2(3n-4)

Simple and best practice solution for 2(5n-8)-5n=2(3n-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(5n-8)-5n=2(3n-4) equation:


Simplifying
2(5n + -8) + -5n = 2(3n + -4)

Reorder the terms:
2(-8 + 5n) + -5n = 2(3n + -4)
(-8 * 2 + 5n * 2) + -5n = 2(3n + -4)
(-16 + 10n) + -5n = 2(3n + -4)

Combine like terms: 10n + -5n = 5n
-16 + 5n = 2(3n + -4)

Reorder the terms:
-16 + 5n = 2(-4 + 3n)
-16 + 5n = (-4 * 2 + 3n * 2)
-16 + 5n = (-8 + 6n)

Solving
-16 + 5n = -8 + 6n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-6n' to each side of the equation.
-16 + 5n + -6n = -8 + 6n + -6n

Combine like terms: 5n + -6n = -1n
-16 + -1n = -8 + 6n + -6n

Combine like terms: 6n + -6n = 0
-16 + -1n = -8 + 0
-16 + -1n = -8

Add '16' to each side of the equation.
-16 + 16 + -1n = -8 + 16

Combine like terms: -16 + 16 = 0
0 + -1n = -8 + 16
-1n = -8 + 16

Combine like terms: -8 + 16 = 8
-1n = 8

Divide each side by '-1'.
n = -8

Simplifying
n = -8

See similar equations:

| 4(n+5)=7(n+8) | | n+1-3n=-(5+n)+1-2n | | 7z-3=32 | | 2(x+5)-4=24 | | 7z-3=42 | | (7x+31)+(21x-19)=180 | | n^2=6n-5 | | 2x+9=-3x-6 | | 5+4p=19 | | 2z-3(z-1)=-(5z+6)+z | | 6y+1=55 | | 8(x-5)=-104 | | (4m+1)(m+2)= | | 4v^2=12v+72 | | (m-1)(m-5)=0 | | 3z+66=z+32 | | 180+28.4=x+x | | 6b^2-30b=0 | | x-2=15-2 | | (11+4x)+2(11+4x)=195 | | 12y-(21-y)=2y | | 1+3n=7n+9 | | 152=-8(-7-4x) | | y+60=2y+6 | | -24+3y=9 | | 28.4+2x=180 | | 2.30=x+x | | (b-5)(b-1)=0 | | -81=-3(4k-5) | | 11z+54=9z+56 | | x+x+28.4=180 | | (v-1)(v-4)=0 |

Equations solver categories